2014
DOI: 10.1016/j.celrep.2014.03.056
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Insulin/IGF-1 Signaling Restores Germ Cell Immortality to Caenorhabditis elegans Piwi Mutants

Abstract: SUMMARY Defects in the Piwi/piRNA pathway lead to transposon desilencing and immediate sterility in many organisms. We found that the C. elegans Piwi mutant prg-1 became sterile after growth for many generations. This phenotype did not occur for RNA interference mutants with strong transposon silencing defects and was separable from the role of PRG-1 in transgene silencing. Brief periods of starvation extended the transgenerational lifespan of prg-1 mutants by stimulating the DAF-16/FOXO longevity transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
172
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(189 citation statements)
references
References 52 publications
7
172
0
Order By: Relevance
“…elegans harbors both prosilencing and antisilencing secondary siRNA systems, where prosilencing 22G-RNAs associate with WAGO-class Argonaute proteins and antisilencing 22G-RNAs associate with ALG-3/-4 and CSR-1 Argonaute proteins. Both these pathways have been implicated in transgenerational sterility phenotypes (26,44). Conine et al reported that heterozygosity for alg-3/-4 or csr-1 mutations in males can elicit a temperature-sensitive mortal germ-line phenotype, apparent only at 25°C (26).…”
Section: Discussionmentioning
confidence: 99%
“…elegans harbors both prosilencing and antisilencing secondary siRNA systems, where prosilencing 22G-RNAs associate with WAGO-class Argonaute proteins and antisilencing 22G-RNAs associate with ALG-3/-4 and CSR-1 Argonaute proteins. Both these pathways have been implicated in transgenerational sterility phenotypes (26,44). Conine et al reported that heterozygosity for alg-3/-4 or csr-1 mutations in males can elicit a temperature-sensitive mortal germ-line phenotype, apparent only at 25°C (26).…”
Section: Discussionmentioning
confidence: 99%
“…This phenotype has not been detected in C. elegans N2, but has been observed in many temperature-sensitive mutants derived from it, affecting : 1) telomere formation and DNA repair (Smelick and Ahmed, 2005;Kirienko et al, 2010), or 2) histone modifications and small RNA synthesis in the germ line (Buckley et al, 2012;Simon et al, 2014). Because germ line small RNAs and histone modifications are transmissible across generations in C. elegans (Grishok et al, 2000;Burton et al, 2011;Gu et al, 2012;Buckley et al, 2012;Ashe et al, 2012;Shirayama et al, 2012;Conine et al, 2013), they could perhaps explain a non-genic transgenerational effect or adaptation.…”
Section: In Today's Lightmentioning
confidence: 99%
“…In C. elegans, the loss of prg-1 leads to transgenerational germline mortality (mrt) (Simon et al, 2014). Briefly, unlike Piwi mutant animals in other organisms, C. elegans prg-1 mutants are not immediately sterile and, when freshly outcrossed, display relatively mild fertility defects while still producing fertile offspring.…”
Section: Pirna Functions Beyond Transposon Silencingmentioning
confidence: 99%